South Korean Trade Strategies in the Post Global Financial Crisis - Park, Sang-Chul (The journal of contemporary issues in business and government, 2014)
Korea has developed rapidly since the 1960s to become one of the four Asian tiger economies. Korea is an example to other nations of how a developing country can develop its economy rapidly and become industrialized. Its development strategy has mainly been based on an export oriented trade policy. As a result, its trade volume has increased from USD1 billion at the beginning of the 1960s to USD1 trillion in 2011, which is a 1,000 time increase within five decades. However, the Korean economy has experienced turbulence as well as positive changes. It has faced severe economic crises such as the Asian financial crisis in 1997 and the global financial crisis in 2008. This paper discusses Korea’s trade policy and the strategies utilized over the last five decades to develop the national economy. It also explores how the government reacted and adapted its policy when the economy was hit by external economic crises. Moreover, it investigates and analyses the role that trade policy and strategy has played in developing the nation’s sustainability.